Pengukuran Overall Equipment Effectiveness untuk Optimalisasi Kinerja Shiploader di Industri Batubara - Aam Wahyu Pratama; Suharto Suharto; Putri Endah Suwarni; Susanti Sundari (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
PT X in Lampung uses a Shiploader as the primary equipment for coal loading operations; however, the high level of downtime has resulted in suboptimal operational effectiveness. This study aims to identify the factors contributing to the low effectiveness of the machine and propose improvement recommendations. The methods employed include Overall Equipment Effectiveness (OEE), Six Big Losses, Fishbone Diagram, and the 5W+1H approach. The results indicate that the average OEE value was 76%, which is below the World Class OEE standard of 85%, with an Availability of 90%, a Performance Rate of 85%, and a Quality Rate of 99%. The Six Big Losses analysis revealed that Reduced Speed Losses accounted for the highest loss at 15.62%, while Equipment Failure Losses were the primary cause of downtime, with a total breakdown time of 4,141 minutes or 13.6%. Improvement recommendations include implementing scheduled preventive maintenance, conducting routine inspections of the oil cooler system, using spare parts that comply with manufacturer specifications, enhancing operator competence through regular training, ensuring compliance with Standard Operating Procedures (SOP), and performing periodic evaluations to improve Shiploader reliability and increase the OEE value. Keywords: Availability, Downtime, Overall Equipment Effectiveness (OEE), Performance, Shiploader